Vitamin D Attenuates Ischemia/Reperfusion-Induced Cardiac Injury by Reducing Mitochondrial Fission and Mitophagy - Lee, Tzu-Lin; Lee, Ming-Hsueh; Chen, Yu-Chen; Lee, Yi-Chieh; Lai, Tsai-Chun; Lin, Hugo You-Hsien; Hsu, Lee-Fen; Sung, Hsin-Ching; Lee, Chiang-Wen; Chen, Yuh-Lien (Frontiers in Pharmacology, 2020)
Myocardial infarction is the leading cause of global morbidity and mortality. Although myocardial reperfusion after ischemia (I/R) is an effective method to save ischemic myocardium, it can cause adverse reactions, including increased oxidative stress and cardiomyocyte apoptosis. Mitochondrial fission and mitophagy constitute the essential factors for mitochondrial quality control, and whether they play the key role in cardiac I/R injury remains elusive. New pharmacological or molecular interventions to alleviate reperfusion injury are a timely desirable therapy. Vitamin D3 (Vit D3) regulates cardiovascular function, but its physiological contribution to I/R-treated hearts, especially its effects on mitochondrial homeostasis, remains unclear. The hypoxia/reoxygenation (H/R) model of H9c2 cells was established in vitro to simulate myocardial I/R injury. H/R treatment significantly reduced the H9c2 cell viability, increased apoptosis, and activated caspase 3. Besides, H/R treatment increased mitochondrial fission, manifested by increased expression of phosphorylated dynein-related protein 1 (p-Drp1) and mitochondrial fission factor (Mff) as well as mitochondrial translocation of Drp1. Treatment with the mitochondrial ROS scavenger MitoTEMPO increased cell viability and reduced mitochondrial fission. H/R conditions elicit excessive mitophagy, such as increased expression of BNIP3 (BCL2 interacting protein 3) and LC3BII/I and observed the formation of a number of autolysosomes. In contrast, Vit D3 reverses these effects. In the mouse I/R model induces apoptosis, mitochondrial fission, and mitophagy. Vit D3 treatment mitigates apoptosis, mitochondrial fission, mitophagy, and myocardial ultrastructural abnormalities. The results indicate that Vit D3 exerts cardioprotective effects against I/R cardiac injury by protecting mitochondrial structural, functional integrity and reducing mitophagy.